Clopidogrel resistance in North Indian patients of coronary artery disease and lack of its association with platelet ADP receptors P2Y1 and P2Y12 gene polymorphisms. (June 2013) - Kar, Rakhee; Meena, Arvind; Yadav, Birendra K.; Yadav, Rakesh; Kar, Sitanshu Sekhar; Saxena, Renu
<x xml:space="preserve">Abstract</x> Aspirin and Clopidogrel are used in prophylaxis of patients undergoing percutaneous coronary intervention and long-term prevention of cardiovascular and cerebrovascular events. Clopidogrel resistance has been attributed to P2Y1 and P2Y12 adenosine diphosphate (ADP) receptor polymorphisms. This study enrolled 100 patients of coronary artery disease (CAD) who were on the maintenance dose of clopidogrel (75 mg OD) with or without aspirin. In addition, 10 received loading dose (300 mg) prior to percutaneous coronary intervention. Relevant clinical and drug history were elicited. ADP-induced platelet aggregation study and PCR-RFLP for P2Y1 (1622A > G) and P2Y12 (i-T744C) polymorphisms were performed. Two groups of controls were used for defining cut-off for platelet aggregation response. Follow-up data, wherever available was recorded. The most common pattern of aggregation response was disaggregation, either complete (46.4%) or partial (53.6%). A frequency of 13% clopidogrel non-responders and 19% semi-responders was found. All the cases were H1/H1 haplotype for P2Y12 gene polymorphism and 28 (29.2%) patients carried P2Y1 1622A > G (21(21.9%) AG and 7(7.3%) GG) gene polymorphism, the frequency being greater in clopidogrel responders compared to semi/non-responders but difference was not statistically significant. There was no statistically significant difference between responders and semi/non-responders in terms of the history of risk factor for CAD, concurrent atorvastatin use or past history of an acute vascular event. On follow up, the two patients who developed myocardial infarction/acute coronary syndromes (MI/ACS) were clopidogrel semi- and non-responder, respectively. Variability in clopidogrel response with 13% non-responders and 19% semi-responders was seen in this study with adverse outcome (MI/ACS) on follow up seen in two patients. Hence, poor response to clopidogrel may be related to increased likelihood of adverse long-term coronary event that may benefit from additional or alternative anti-platelet therapy. Clopidogrel resistance was not associated with ADP receptor P2Y1 and P2Y12 gene polymorphisms. Hence, it is postulated that clopidogrel resistance in CAD patients is multifactorial and not caused by single-gene polymorphisms.